Leaders’ Emotional Intelligence, Teachers’ Academic Optimism And Organisational Commitment In Malaysian Secondary Schools - Vetriveilmany, Uma Thevi (2021)
Emotional intelligence – identified by previous study as an aspect that importance for leader to lead subordinate in achieving the aspiration and goals of organisation. Educational institutions require sound leadership as well as optimistic and committed teachers, working in harmony, unison and complementarity with each other. The main purpose of this study is to examine the emotional intelligence of school leaders (LEI) in Malaysia and its influence on teachers’ academic optimism (TAO) and teachers’ organisational commitment (TOC) in secondary schools. In addition, the study also examined the role of teachers’ academic optimism as a mediator on the relationship between leaders’ emotional intelligence and teachers’ organisational commitment. Based on the quantitative data collection methods, the study adopted a cross-sectional survey design. A total of 385 secondary school teachers from northern zone of Peninsular Malaysia; Kedah, Perak, Perlis and Penang were selected as respondents using random sampling method. A set of questionnaire which comprises the Emotional Leadership Questionnaire (ELQ), the Teachers Sense of Academic Optimism for Secondary Teachers (TAOS-S) and the Multi-dimensional Commitment to Educational Organisational -Teacher Questionnaire- were employed as the intrument for data collection. Data were analysed using descriptive analysis and inferential statistics. The findings showed that the emotional intelligence of school leaders (M=4.30, SD=.42) and academic optimism of teachers (M=4.29, SD=.53) are at high level.